2017
DOI: 10.1016/j.molmet.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial pyruvate carrier mediates high fat diet-induced increases in hepatic TCA cycle capacity

Abstract: ObjectiveExcessive hepatic gluconeogenesis is a defining feature of type 2 diabetes (T2D). Most gluconeogenic flux is routed through mitochondria. The mitochondrial pyruvate carrier (MPC) transports pyruvate from the cytosol into the mitochondrial matrix, thereby gating pyruvate-driven gluconeogenesis. Disruption of the hepatocyte MPC attenuates hyperglycemia in mice during high fat diet (HFD)-induced obesity but exerts minimal effects on glycemia in normal chow diet (NCD)-fed conditions. The goal of this inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 44 publications
5
83
0
Order By: Relevance
“…Both MPC1 and MPC2 mouse knockout models display embryonic lethality during midgestation (21,31) and MPC1 hypomorphs caused early perinatal lethality (20). In contrast, postnatal liver-specific MPC disruption attenuates obesity-induced hyperglycemia (11,12) and decreases fibrosis and inflammation in mouse models of nonalcoholic fatty liver disease (NAFLD) and NASH (14,32). The contrast between the clearly pathological effects of whole-body MPC disruption during prenatal development versus potential therapeutic effects of liver MPC disruption after development highlights the need to better understand tissue-specific pyruvate metabolism across developmental stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both MPC1 and MPC2 mouse knockout models display embryonic lethality during midgestation (21,31) and MPC1 hypomorphs caused early perinatal lethality (20). In contrast, postnatal liver-specific MPC disruption attenuates obesity-induced hyperglycemia (11,12) and decreases fibrosis and inflammation in mouse models of nonalcoholic fatty liver disease (NAFLD) and NASH (14,32). The contrast between the clearly pathological effects of whole-body MPC disruption during prenatal development versus potential therapeutic effects of liver MPC disruption after development highlights the need to better understand tissue-specific pyruvate metabolism across developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the liver MPC lowers blood glucose during diabetes (11,12), and attenuates non-alcoholic steatohepatitis (NASH; refs. 13,14). Conversely, decreased MPC expression and activity increases stemness in some cancers (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Pierelli et al (59) demonstrated that hyperglycemia-induced downregulation of uncoupling protein 2 expression impairs mitochondrial membrane potential and induces energy metabolism disorder. Besides, suppression of the mitochondrial tricarboxylic acid cycle due to chronic high glucose injury causes energy undersupply (60) and results in abnormal lipid metabolism. Similar to these reports, the present study demonstrated that high glucose induced excessive ROS production and impaired the glomerular anti-oxidative system, resulting in opening of the mPTP.…”
Section: Discussionmentioning
confidence: 99%
“…Because MPC1 and MPC2 associate in an oligomer, loss of either protein can impair the stability of the other, resulting in loss of MPC function (Bender, Pena, & Martinou, 2015;Bricker et al, 2012;Herzig et al, 2012). In high fat diet-fed mice, MPC mediates increased hepatic mitochondrial pyruvate utilization, contributing to hyperglycaemia and liver fibrosis (Rauckhorst et al, 2017). In diabetic mice, MPC function is enhanced to ensure efficient gluconeogenesis while loss of MPC activity attenuates hyperglycaemia (Gray et al, 2015;McCommis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%